Full resistance and decreased susceptibility to carbapenems in IMP-13-producing Pseudomonas aeruginosa isolates from an outbreak - Santella, Gisela (2010)
Of 23 ceftazidime-resistant Pseudomonas aeruginosa isolates with simultaneous decreased susceptibility to carbapenems recovered from inpatients at Hospital Eva Peron, Provincia de Buenos Aires, Argentina, from December 2004 to December of 2005, 18 were positive by a double-disk phenotypic screening of metallo-β-lactamases (MBLs) using EDTA (1 μmol) (6). Decreased susceptibility was defined as to refer to isolates with MICs of 2 to 8 μg/ml or inhibition zones of 16 to 21 mm, categorized as susceptible or intermediate according CLSI breakpoints, but which clearly differed from fully susceptible isolates.